Biodiversity of green unicellular algae, Haematococcus pluvialis based on inter-simple sequence repeat (ISSR) markers - Noroozi, Mostafa; Tan, Soon Guan; Napis, Suhaimi; Omar, Hishamuddin (2009)
Haematococcus pluvialis is unicellular green algae which consider as best astaxanthin producer organism. Recently scientists have discovered that Haematococcus, unicellular green algae is one of the organisms that produced astaxanthin. DNA extracted from 10 different strains (4 strains from Iran and 6 strains from CCAP) and genetic diversity carried out using 10 ISSR primers. The results showed that polymorphism between collected Haematococcus pluvialis. Range of produced bands was between 3.4 to o.14 Kb. Highest and lowest ration of polymorphism were in primers (4, 5, 7, 10, 17, and 18) and 14 respectively. Highest genetic distance found between 8 And 4 Strains and lowest genetic distance between strains 7 and 2. Preliminary results showed ISSR markers can be good candidate markers for study of Haematococcus.